Hydroponic Nutrient Film Technique (NFT) System Based on Automation in Ciparay Village - Waluyo, Waluyo; HADIATNA, FEBRIAN; YUONO, YUONO (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
Hydroponics is a farming technique that has many advantages. This system has many types, for example the Nutrient Film Technique (NFT). In this activity, an NFT hydroponic system based on automation is created for parameter settings that affect plant growth. Several parameters are controlled, such as pH and TDS on plant nutrition, as well as humidity and air temperature in the environment. This system was placed in Ciparay village to help the community learn hydroponic farming. As a result of this activity, the entire system can work well, but there are still some leaks. After this system worked, socialization activities were carried out to the Ciparay community to explain how to use the system for hydroponic cultivation.